The relationship between prophetic preaching and performing the gift of prophecy in South Africa - Klerk, Ben J. de (HTS teologiese studies, 2013)
The goal of this article is to investigate the relationship between the liturgy of the worship service, where prophetic preaching is delivered, and the liturgy of life, where the gift of prophecy must be put into practice. In what way could the ‘prophets’ be equipped to become practitioners of the gift of prophecy? A short description is given of what is understood by prophetic preaching and the gift of prophecy in an effort to determine the relationship between these concepts. In a brief summary, burning questions in church life and in the South African society are addressed: in church life, the questions of extreme conservatism and extreme liberalism are scrutinised and in the South African society, corruption and inequality are investigated. In conclusion, a few guidelines are given for putting the gift of prophecy into practice in the liturgy of life.